Consequences of hydroxyl generation by the silica/water reaction Part II: Global and local Swelling - Part III: Damage and Young's Modulus - Fett, Theo (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
Water diffusing into silica surfaces gives rise for several effects on diffusion behaviour and mechanical properties. In a preceding booklet, we focused on diffusion and fiber strengths and deformations which were obtained by water soaking under external loading. In the present booklet we deal with results and interpretations of strength increase in the absence of applied stresses.